Pengaruh Variasi Diameter Torak terhadap Performansi Sepeda Motor Bertransmisi Manual - I Gede Billy Arya Pratama; I Gede Wiratmaja; Nyoman Arya Wigraha (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2023)
This research is an experimental study conducted to determine the effect of variations in piston diameter on the performance of manual transmission motorbikes. The independent variables in this study are variations in the diameter of the piston with initial conditions 52.5 mm to 53 mm (modification 1) and 53.5 mm (modification 2). Then, the dependent variables in this study are torque, power, and fuel consumption. Torque and power tests were carried out using the dyno test equipment, and fuel consumption testing was done using a measuring cup and calculating the mass of fuel per unit of time; then, the research data was analyzed using quantitative descriptive techniques. In theory, changing the size of the piston affects the compression ratio, which in turn affects the vehicle's performance. After the research, it is known that there is an effect of variation in piston diameter on torque, power, and fuel consumption, where the highest torque is achieved in the use of a modified piston on 53.5 mm by 12.49%, then the highest power is achieved by 7.02%, and the highest fuel consumption is achieved by 17.15%.